2018
DOI: 10.1002/ajpa.23388
|View full text |Cite
|
Sign up to set email alerts
|

Developments in development: What have we learned from primate locomotor ontogeny?

Abstract: The importance of locomotion to evolutionary fitness has led to extensive study of primate locomotor behavior, morphology and ecology. Most previous research has focused on adult primates, but in the last few decades, increased attention to locomotor development has provided new insights toward our broader understanding of primate adaptation and evolution. Here, we review the contributions of this body of work from three basic perspectives. First, we assess possible determinants on the timing of locomotor inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 367 publications
(596 reference statements)
0
36
0
Order By: Relevance
“…It has been observed that only 2 weeks after birth, mouse lemurs begin to explore their environment and already use narrow substrates requiring a strong grip to maintain balance (Colas, ). The relatively large and robust extremities of juveniles provide stability during arboreal locomotion with a reduced risk of falling and subsequent skeletal injury (Young & Shapiro, ). Byron et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that only 2 weeks after birth, mouse lemurs begin to explore their environment and already use narrow substrates requiring a strong grip to maintain balance (Colas, ). The relatively large and robust extremities of juveniles provide stability during arboreal locomotion with a reduced risk of falling and subsequent skeletal injury (Young & Shapiro, ). Byron et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that only 2 weeks after birth, mouse lemurs begin to explore their environment and already use narrow substrates requiring a strong grip to maintain balance (Colas, 1999). The relatively large and robust extremities of juveniles provide stability during arboreal locomotion with a reduced risk of falling and subsequent skeletal injury (Young & Shapiro, 2018). Byron et al (2015) showed that mice raised in enclosures with fine branch arboreal substrates displayed more robust foot bones than ones raised on the ground and that did not need to use their hallux to grasp substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a difference in relative gestation duration between the ape and non-ape clades contrasts with the lactation duration results suggests that the distinctive feature of ape life history is a different lactation and postnatal development strategy. Together, these results may help to explain the combination of unusually large cerebella (23) extended periods of immaturity (26) delayed locomotor independence (49), and high levels of social learning (50) and play (51) found an association between hippocampal neurogenesis cessation and lifespan across a range of rodent and primate taxa, and thus across a range of life history patterns (53). In contrast, an early examination of the life history correlates of structure sizes found that hippocampus volume correlated with female age at first parturition but not lifespan in primates (13), however these early analyses were non-phylogenetic and used residuals to correct for allometry, both of which can bias parameter estimates (33,54).…”
Section: Model Comparisons Using Aic (Simentioning
confidence: 94%
“…Laboratory studies have provided extensive data on the biomechanics of primate quadrupedal locomotion on simulated arboreal and terrestrial substrates (e.g., Carlson & Demes, ; Demes, ; Hesse, Nyakatura, Fischer, & Schmidt, ; Larson, Schmitt, Lemelin, & Hamrick, ; Nyakatura, Fisher, & Schmidt, ; Schmidt, ; Schmitt, ; Schoonaert et al, ; Shapiro, Kemp, & Young, ; Shapiro & Raichlen, ; Stevens, ; Vereecke, D'Août & Aerts, ; Young, ; Young, Stricklen, & Chadwell, ), and have been critical in exploring various hypotheses of primate origins and gait kinematics in a controlled setting. For example, laboratory studies have demonstrated that primates typically use diagonal sequence, diagonal couplet gaits across substrates of various diameters and orientations (Cartmill, Lemelin, & Schmitt, ; Cartmill, Lemelin, & Schmitt, ; Lemelin & Schmitt, ; Lemelin, Schmitt, & Cartmill, ; Nyakatura, Fischer, & Schmidt, ; Nyakatura & Heymann, ; Schmidt, ; Shapiro & Raichlen, ; Shapiro, Young, & Souther, ; Stevens, ; Wallace & Demes, ; Young, ; Young & Shapiro, ). Laboratory studies have also demonstrated that primates adjust gait type, limb kinematics, and limb force distribution when moving on different substrate types (i.e., flat surface vs. cylindrical), in response to changes in diameter or orientation of cylindrical substrates (Carlson & Demes, ; Hesse et al, ; Nyakatura et al, ; Schmitt, ; Schmitt & Hanna, ; Shapiro et al, ; Young, ), and in response to the interactions among substrate conditions (e.g., Shapiro, Young, & VandeBerg, ; Young et al, ).…”
Section: Introductionmentioning
confidence: 99%